Size effect in curing optimization for thick composite laminates. (March 2023) - Gao, Yan; Lin, Zequn; Zhou, Yanquan; Ling, Zihan; Dong, Jiale; Wang, Huan; Peng, Hua-Xin
Abstract: The component size has a profound effect on curing optimization for thick composite laminates where the curing behavior is closely related to the thickness. The present study was set out to correlate the constraints, optimization objects and curing parameters with varying component size. The Pearson's correlation coefficient was adopted to illuminate the sensitivity of curing parameters to specimen's size. The results indicate that the increase of the first dwell temperature ( CT 1 ) and time ( t 1 ) can improve the curing quality and the increase of the first heating rate ( r 1 ) can significantly reduce the cure time. The selection criterion of the second dwell temperature ( CT 2 ) and heating rate ( r 2 ) depend heavily on two constraints and component size. It was found that the Pearson's correlation coefficient can qualitatively reflect the change of curing parameters and provide guidance for the optimization of curing process. Graphical Abstract: ga1 Highlights: A multi-objective optimization strategy has been used for curing thick composite laminates. The sensitivity of curing parameters to specimen's geometry is illuminated by the Pearson's correlation coefficient. The size effect in curing optimization for thick composite laminates has been elucidated.